Pencapaian Standar Isi: Tantangan Bagi Guru Madrasah - Euis Rosita; Chaerul Rochman; Ida Farida; Agus Salim Mansur (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2020)
This study aims to determine the achievement of the Contents Standards through the understanding of PAI and Non PAI teachers in each Indicator. The Population in this study is Madrasah Ibtidaiyah in Tasikmalaya Regency and its samples are MI Tarbiyatul Ula and MI Al-Muawanah. This research method uses descriptive quantitative. Data collection techniques using observation, questionnaire documentation and data analysis. Data collection and observation using google form distributed to 5 PAI teachers and 5 Non PAI teachers. Collecting authentic data and triangulating interview results with several teachers and analyzing the results of comparisons between PAI and Non PAI teachers. The results of this study indicate that achievement of the contens of 84,50 % for PAI teachers and 82,00 % for Non PAI teachers. This shows the level of achievement of the Contents Standards through teacher understanding through each indicator is still lacking and needs to be improved by following various training and teacher readinessto improve performance.